Kosovo and Serbia: an agreement to normalize relations - Siegertszt, Sidney Robin (2021)
This paper was conducted through qualitative field research in Kosovo and Serbia. The sources of the information obtained through interviews will remain anonymous at the request of European Union (EU) representatives and diplomats. The paper briefly narrates the historical events that led to the creation of the First Agreement of Principles Governing the Normalization of Relations of Kosovo and Serbia with an in-depth assessment of Article 1 and its implementation process. The European Union played a crucial role as the main mediator between the countries, but is not exempt from criticism. Article 1 of the First Agreement defines the creation of an Association/Community of Serb majority municipalities in the northern region of Kosovo with its own statute and competences. The focus of this article is to ascertain what the determinants were for Kosovo, Serbia and the EU to sign the First Agreement and the importance of Article 1 and its implications for all parties involved.